2011
DOI: 10.1192/bjp.bp.110.082065
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national clinical and functional remission rates: Worldwide Schizophrenia Outpatient Health Outcomes (W-SOHO) study

Abstract: Clinical outcomes of schizophrenia seem to be worse in Europe compared with other regions. However, functional remission follows a different pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(85 citation statements)
references
References 41 publications
(51 reference statements)
3
79
2
1
Order By: Relevance
“…The total sample of patients was 14 192, including over half of the patients from the W‐SOHO study that reported a small, but significant relationship between age at onset and the outcome (Haro et al, 2011). One study reported in 2 papers indicated an opposite significant relationship between the variables (Bland & Parker, 1978; Bland et al, 1976).…”
Section: Resultsmentioning
confidence: 99%
“…The total sample of patients was 14 192, including over half of the patients from the W‐SOHO study that reported a small, but significant relationship between age at onset and the outcome (Haro et al, 2011). One study reported in 2 papers indicated an opposite significant relationship between the variables (Bland & Parker, 1978; Bland et al, 1976).…”
Section: Resultsmentioning
confidence: 99%
“…22 Recent report from SOHO (Schizophrenia Outpatient Health Outcome), including 10 studies from Western Europe and 27 studies from 4 different continents, suggests that clinical remission was significantly lower in Europe compared with other regions, but this difference was not found for functional remission. 38 More research from the developing world will help resolve these issues, and in this context, it is gratifying to see more high quality outcome studies now emerging from these sites. 38,39 In the meta-analysis of Hegarty et al 15 studies, using broad non-Kraepelinian criteria showed better outcomes than those using narrow Kraepelinian criteria.…”
Section: Discussionmentioning
confidence: 99%
“…38 More research from the developing world will help resolve these issues, and in this context, it is gratifying to see more high quality outcome studies now emerging from these sites. 38,39 In the meta-analysis of Hegarty et al 15 studies, using broad non-Kraepelinian criteria showed better outcomes than those using narrow Kraepelinian criteria. We did not find clear support for this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison results were drawn from the literature, outside the primary setting. We reviewed prospective and retrospective cohort studies of the natural course of schizophrenia and bipolar disorder from low-income countries (Thirthalli et al, 2009, Haro et al, 2011, Ran et al, 2001) and selected one from Ethiopia (Kebede et al, 2005) for being closest in context.…”
Section: Methodsmentioning
confidence: 99%